Persepsi Guru Terhadap Partisipasi Siswa Pada Mata Pelajaran Sejarah Di SMAN 2 Koto XI Tarusan - Yudia Elvira; Zafri Zafri (Jurnal Kronologi, 2021)
Abstract This research is motivated by various problems regarding student participation. The problem is 1) the incomplete participation of students in learning history at SMA Negeri 2 Koto XI Tarusan. 2) Students only focus on listening to the teacher's explanation. This study aims to determine how the teacher's impression of student participation in history learning, then what is the obstacle to student participation is not yet perfect. This method is used in descriptive research with a quantitative approach, the source of the data in this study is obtained directly from information in the field through distributing questionnaires to history teachers at SMA Negeri 2 Koto XI Tarusan. The findings of this study indicate that student participation is in the good category with a score of 76%. The results of the study in general, the percentage of teacher impressions on student participation in each class was in the very good category, there were 17 classes with a percentage of 50%, in the good category there were 13 classes with a percentage of 38%, while in the medium category there were 4 classes with a percentage of 12%. In the less and very less category, the teacher's impression of student participation does not exist at all.